2002
DOI: 10.2166/wst.2002.0532
|View full text |Cite
|
Sign up to set email alerts
|

The effect of C/N ratio on ammonia oxidising bacteria community structure in a laboratory nitrification-denitrification reactor

Abstract: A laboratory scale reactor operated as a single sludge, denitrification-nitrification bioreactor (DNB), was fed a synthetic wastewater. The effect of the C/N ratio of the influent on the structure of beta-proteobacterial autotrophic ammonia-oxidizing bacterial (AOB) communities was determined by DGGE analysis of 16S rRNA gene fragments amplified using a range of AOB-selective primers. Fluorescence in situ hybridisation (FISH) was used to determine quantitative changes in the AOB communities. When operated at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…Many physical and geochemical factors influence nitrification, including oxygen concentrations (e.g. Christensen et al ., 1990), sulfide concentrations (Joye and Hollibaugh, 1995), Fe(III) content (Dollhopf et al ., 2005), salinity (Rysgaard et al ., 1999; Caffrey et al ., 2003; Bernhard et al ., 2007), C:N ratios (Ballinger et al ., 2002), availability of ammonium (e.g. Jones and Hood, 1980), light (Horrigan and Springer, 1990) and temperature (Berounsky and Nixon, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Many physical and geochemical factors influence nitrification, including oxygen concentrations (e.g. Christensen et al ., 1990), sulfide concentrations (Joye and Hollibaugh, 1995), Fe(III) content (Dollhopf et al ., 2005), salinity (Rysgaard et al ., 1999; Caffrey et al ., 2003; Bernhard et al ., 2007), C:N ratios (Ballinger et al ., 2002), availability of ammonium (e.g. Jones and Hood, 1980), light (Horrigan and Springer, 1990) and temperature (Berounsky and Nixon, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Nitrosomonas were dominant AOB in both wastewater treatment plants Juretschko et al 1998;Dionisi et al 2002;Hallin et al 2005) and bench-scale systems (Okabe et al 1999;Bouchez et al 2000;Ballinger et al 2002;Nogueira et al 2002;Tsuneda et al 2003), while Nitrosospira were dominant mainly in bench-scale systems (Schramm et al 1998(Schramm et al , 1999You et al 2003). It has been reported that Nitrosomonas were dominant AOB in both wastewater treatment plants Juretschko et al 1998;Dionisi et al 2002;Hallin et al 2005) and bench-scale systems (Okabe et al 1999;Bouchez et al 2000;Ballinger et al 2002;Nogueira et al 2002;Tsuneda et al 2003), while Nitrosospira were dominant mainly in bench-scale systems (Schramm et al 1998(Schramm et al , 1999You et al 2003).…”
Section: The Shift Of Dominant Aob and Nob Groupsmentioning
confidence: 98%
“…Relevant operational parameters of these plants are summarized in Table 1. The laboratory reactor is described in detail elsewhere (4,5).…”
Section: Activated Sludge Plantsmentioning
confidence: 99%